Teachers’ interpretations on Task-Based Language Teaching (TBLT) in the inter-cultural English language classroom - Abdullah, Liza (2011)
Task-Based Language Teaching (TBLT) has been applied to many English language curriculums across Asia. However, little research has been done to explore what teachers know and believe about these reforms in their specific contexts. This paper explores the interpretations of teachers on the methodology through interviews for data collection. The findings on how teachers feel about the implementation of the methodology in line with their expectations on students at the end of a semester were presented. The implication of the study is more towards how to go about strengthening the curriculum to realise the vision of all the English Language teachers at large.